Fine-Tunable and Injectable 3D Hydrogel for On-Demand Stem Cell Niche - Hong, Ki Hyun; Kim, Young-Min; Song, Soo-Chang (WILEY, 2019)
Stem-cell-based tissue engineering requires increased stem cell retention, viability, and control of differentiation. The use of biocompatible scaffolds encapsulating stem cells typically addresses the first two problems. To achieve control of stem cell fate, fine-tuned biocompatible scaffolds with bioactive molecules are necessary. However, given that the fine-tuning of stem cell scaffolds is associated with UV irradiation and in situ scaffold gelation, this process is in conflict with injectability. Herein, a fine-tunable and injectable 3D hydrogel system is developed with the use of thermosensitive poly(organophosphazene) bearing beta-cyclodextrin (beta-CD PPZ) and two types of adamantane-peptides (Ad-peptides) that are associated with mesenchymal stem cell (MSC) differentiation and that serve as stoichiometrically controlled pendants for fine-tuning. Given that complexation of hosts and guests subject to strict stoichiometric control is achieved with simple mixing, these fabricated hydrogels exhibit well-aligned, fine-tuning responses, even in living animals. Injection of MSCs in fine-tuned hydrogels also results in various chondrogenic differentiation levels at three weeks postinjection. This is attributed to the differential controls of Ad-peptides, if MSC preconditioning is excluded. Eventually, the fine-tunable and injectable 3D hydrogel could be applied as platform technology by simply switching the types of peptides bearing adamantane and their stoichiometry.
Keywords: N-CADHERIN; PROTEIN-KINASE; CHONDROGENESIS; DIFFERENTIATION; P38; DELIVERY; NANOPARTICLES; STRATEGIES; TGF-BETA-1; SCAFFOLDS